2021
DOI: 10.1155/2021/5580672
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine Enhances Aerobic Glycolysis and May Act as a Predictive Factor for Immunotherapy in Gastric Cancer

Abstract: Objective/Background and Aims. The gastrointestinal tract is rich in neurotransmitters, which play an essential role in the occurrence and development of gastrointestinal tumors. We aimed to explore the function of neurotransmitters in gastric cancer and identify a suitable target to treat gastric cancer patients in the future. Methods. Monoamine neurotransmitters were detected in gastric cancer tissue and paired normal tissue, and The Cancer Genome Atlas was used to identify differentially expressed norepinep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
1
6
1
Order By: Relevance
“…In contrast to our data, decreasing the MAO-B level was reported in BC and many other cancers [19]. Nevertheless, the MAO-B expression diminished in gastrointestinal [31] and oral squamous cell carcinoma [32]. In this regard, evidence from human and animal studies indicated that the MAO expression has been regulated by estrogen.…”
Section: Resultscontrasting
confidence: 99%
“…In contrast to our data, decreasing the MAO-B level was reported in BC and many other cancers [19]. Nevertheless, the MAO-B expression diminished in gastrointestinal [31] and oral squamous cell carcinoma [32]. In this regard, evidence from human and animal studies indicated that the MAO expression has been regulated by estrogen.…”
Section: Resultscontrasting
confidence: 99%
“…MAO-A and MAO-B appeared to be expressed in low levels. The high levels of norepinephrine and low MAO-B expression could be a good target for immune therapy [ 69 ].…”
Section: Mao-b’s Role In Cancermentioning
confidence: 99%
“…The biological functions of catecholamines are mediated by adrenergic receptor (AR) families, with β2-AR being the main type expressed in GC [ 55 ]. The levels of noradrenaline and the expression of β2-AR were aberrantly elevated in GC tissues compared with adjacent normal gastric mucosa [ 55 , 56 ]. Catecholamines were shown to enhance the ability of primary GC cells to migrate to the liver and lung to form metastases, while propranolol can abolish the formation of metastatic lesions [ 55 ].…”
Section: Mechanisms Underlying the Increased Recurrence Rate Resultin...mentioning
confidence: 99%